Fusarium culmorum isolated from rhizosphere of wooly cupgrass (Eriochloa villosa) in Debrecen (East Hungary) - Tóth, Tamás; Szilágyi, Arnold (Acta Agraria Debreceniensis, 2016)
Wooly cupgrass (Eriochloa villosa) is an East-Asian originated weed species and it has been spreaded worldwide by now. The first occurrence of this species in Hungary was observed and published in 2008 nearby Gesztely village (Borsod-Abaúj-Zemplén county, North-East Hungary) than in the summer of 2011 a significant population was discovered next to Debrecen city (Hajdú-Bihar county, East Hungary). In 2013 this weed was also reported from Szentborbás village, Somogy county (South-West Hungary). These observations of spreading and its biological features (production of stolons and large number of seeds, moreover herbicide tolerance) indicate that wooly cupgrass (E. villosa) has a great potential of invasiveness, so it may become a hazardous weed not only in Hungary but in all over the world. The objective of this study was to identify the fungus which was isolated from wooly cupgrass (E. villosa) root residue samples which were collected after maize harvesting on arable land in late autumn, near Debrecen. The identification of the fungus based on morphological characters of colonies and the features of conidia developed on potato dextrose agar (PDA) plates. After the examination of axenic culture we revealed that the fungus from rhizosphere of wooly cupgrass was Fusarium culmorum. Pathogenicity and/or endophytic relationship between the fungus and wooly cupgrass is still uncertain so pathogenicity tests and reisolations from plants are in progress.